2018
DOI: 10.1161/circulationaha.118.034464
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Arterial Grafting Is Associated With Better Outcomes for Coronary Artery Bypass Grafting Patients

Abstract: Background: Observational studies have shown better survival in patients undergoing coronary artery bypass grafting (CABG) with 2 arterial grafts compared with 1. However, whether a third arterial graft is associated with incremental benefit remains uncertain. We sought to analyze the outcomes of 3 versus 2 arterial grafts during CABG. As a secondary objective, we compared CABG with 2 or 3 arterial grafts (multiple arterial grafts [MAG]) with CABG using a single arterial graft (SAG). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 32 publications
2
50
1
1
Order By: Relevance
“…The theoretical framework is that, if one arterial graft is better than SVG, then two or even three arterial grafts should have incrementally greater survival, and this contention is supported by multiple publications [38][39][40] . In our own national database analysis, we conducted a series of large-scale propensity score matches using 17 variables.…”
Section: Is Multi-arterial Grafting Significantly Better Than Single mentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical framework is that, if one arterial graft is better than SVG, then two or even three arterial grafts should have incrementally greater survival, and this contention is supported by multiple publications [38][39][40] . In our own national database analysis, we conducted a series of large-scale propensity score matches using 17 variables.…”
Section: Is Multi-arterial Grafting Significantly Better Than Single mentioning
confidence: 99%
“…The relationship between graft failure and reduced survival has a plausible mechanism and therefore it is suggested that the conduit of most interest is the SVG rather than the arterial conduits [37,38,40,45,46] . It would be logical, therefore, that the number of SVG grafts has greater effect on survival than the number of arterial grafts.…”
Section: Count the Veins Not The Arteriesmentioning
confidence: 99%
“…34 As discussed, although a large body of observational data suggests that a second arterial conduit is associated with improved survival, graft patency, and freedom from reintervention, the findings of randomized studies have been equivocal. [4][5][6]17,18,[20][21][22][23][24][25][26][27][28]31 For those surgeons convinced by the available evidencebase, an important factor limiting use of MAG may be technical expertise. The extent of and reason for this gap in practice are not apparent from simply analyzing surgeon case-volume and revascularization strategy.…”
Section: Potential Reasons For the Slow Adoption Of Mag By The Surgicmentioning
confidence: 99%
“…Findings from this study are consistent with recent work from our group showing no difference in late mortality in 2789 propensity score matched pairs comparing 3 arteries vs 2 arteries (HR: 1.08 [95% CI, 0.90-1.29], mean/ maximum follow-up 4.2/8.5 years). 10 On the contrary, a meta-analysis of 8 propensity score-matched observational studies suggests that 3 arterial grafts were associated with a lower risk of late death (HR, 0.80; 95% CI, 0.75-0.87) 11 compared with use of 2 arteries. Similarly, a metaanalysis of randomized clinical trials and observational studies suggested that late mortality was modestly reduced with total arterial revascularization compared with CABG with 2 arteries (incident rate ratio, 0.85; 95% CI, 0.73-0.99).…”
Section: Derrick Y Tam MD and Stephen E Fremes Md Msc Frcsc Fmentioning
confidence: 99%